Fault Tree Analysis of floating offshore wind turbines - Kang, Jichuan; Sun, Liping; Guedes Soares, C. (Renewable energy, 2019)
With the development of offshore wind power, the reliability analysis of offshore wind turbines is increasingly significant due to the system complexity and negative impacts in harsh operating conditions. In this study, the Fault Tree Analysis method is adopted for both qualitative and quantitative evaluation of semi-submersible floating offshore wind turbine failure characteristics. The floating offshore wind turbine is divided into several assemblies, including support structures, pitch and hydraulic system, gearbox, generator and the other systems. Failure rates of relevant offshore structures are collected from previous studies, reports and reliability databases. On this basis, the quantitative assessment of Minimum Cut Sets and Importance Measures are achieved. The calculated results are generally in conformity with statistical data, indicating that most of the failures are caused by several basic factors. Marine conditions, especially the salt-spray and high wind speed, show the most significant impact on floating offshore wind turbine performance. •Fault Tree Analysis method is proposed for evaluation of floating offshore wind turbine failure.•The floating offshore wind turbine is divided into several assemblies.•Failure rates of relevant offshore structures are collected from previous studies.•Quantitative assessment of Minimum Cut Sets and Importance Measures are achieved.•Salt-spray and high wind speed, show the most significant impact on wind turbine performance.